THE DIFFERENCE INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE WITH DEEP TISSUE MASSAGE AND CONTRACT-RELAX STRETCHING TO IMPROVE RANGE OF MOTION CERVICAL JOINT IN MYOFASCIAL PAIN SYNDROME UPPER TRAPEZIUS MUSCLE AT SMA NEGERI 1 SEMARAPURA - Hendrawan, I Gede Donny; Wahyuni, Nila; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Myofascial pain syndrome is a collection of sensory, motor, and autonomic symptoms that cause local and reffered pain, limited range of motion and weakness of the affected muscles. The limitations range of motion will be annoying than the daily activities. Interventions that can improve range of motion of cervikal are Integrated Neuromuscular Inhibition Technique, Deep Tissue Massage and Contract-Relax Stretching. The results show Group Neuromuscular Inhibition Technique with Wilcoxan Sign Rank Test obtained a mean difference of 13.7 with p = 0.000, while the test results Hypothesis Group Contract-Relax Stretching with Paired Sample T-test showed a mean difference of 12.1 with p = 0.000. Test the difference between Mann Whitney U-test showed no significant difference between the other group are obtained p = 0.420. These results indicate that there is no difference in increasing range of motion in both groups. Keywords: Range of motion of cervical, Upper Trapezius Muscle,Myofascial Pain Syndrome, Integrated Neuromuscular Inhibition Technique, Deep Tissue Massage, Contract-relax Stretching, Goniometer